Features of the Epidemiological Situation on Tick-Borne Rickettsioses in the Russian Federation in 2010–2020 and Prognosis for 2021 - N. V. Rudakov; S. N. Shpynov; N. A. Pen’evskaya; A. I. Blokh; T. A. Reshetnikova; I. E. Samoylenko; L. V. Kumpan; S. V. Shtrek; D. A. Savel’ev; N. V. Abramova; D. V. Trankvilevsky; Н. В. Рудаков; et al. (Problems of Particularly Dangerous Infections, 2021)
Objective is to analyze the incidence of Siberian tick typhus (STT) in the Russian Federation over the period of 2010–2020, Astrakhan spotted fever (ASF) and Mediterranean fever (MF) since the official registration, and to forecast the development of the epidemic process for endemic rickettsioses for 2021. The analysis of the incidence of STT, ASF and MF in Russia for the period of 2010–2020, 2013–2020 and 2014–2020, respectively, has been carried out. The forecast of endemic rickettsioses morbidity in the European and Asian parts of Russia for 2021 has been made. The average long-term incidence of STT for 2010–2020 in the Russian Federation as a whole was 1.04 (CI95 1.02÷1.05) 0/0000, with no tendency to change. The maximum relative incidence of STT is typical for the Siberian Federal District (SFD), where the average long-term incidence rate for 2010–2020 was 6.20 (CI95 6.08÷6.31) per 100 thousand of the population. The Far Eastern Federal District (FEFD) – 4.70 (CI95 4.53÷4.87) 0/0000 came in second place, the third place was taken by the Ural Federal District (UFD) – 0.08 (CI95 0.07÷0.10) 0/0000. When assessing the 11-year dynamics of the relative incidence of STT by the Federal Districts, we have detected a tendency to its stabilization in the SFD and the FEFD. In the UFD, a significant downward trend was revealed. The upward trend in the incidence of STT remained in the Altai Republic. Major decline in STT incidence was observed in the Kurgan Region, Trans-Baikal Territory, Krasnoyarsk Territory, and the Republic of Khakassia. There was a declining trend in the incidence of Astrakhan spotted fever in the Astrakhan Region and the Republic of Kalmykia. In the Republic of Crimea and the city of Sevastopol there is no trend to increase the incidence of Mediterranean fever. Цель обзора – проанализировать заболеваемость сибирским клещевым тифом (СКТ) в Российской Федерации в период с 2010 по 2020 год, астраханской пятнистой лихорадкой (АПЛ) и средиземноморской лихорадкой (СЛ) с момента официальной регистрации, ...